2009
DOI: 10.1002/ajhb.20894
|View full text |Cite
|
Sign up to set email alerts
|

Grandparental investment: The influence of reproductive timing and family size

Abstract: The influence that grandparents have on the life history traits of their descendants has been studied extensively. However, no attention has been paid to the potential influence a grandparent's own reproductive history has on the investment they make in their grandchildren. We use data from 658 Swiss grandchildren and 591 of their grandparents to investigate whether grandparents' reproductive scheduling and family size influence the amount of investment grandparents make in a focal grandchild (shared contacts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Previous research has shown that larger sibships lead to dilution of resources directed toward children and grandchildren (Coall et al 2009;Lawson and Mace 2009), reflecting the dynamics of a quality-quantity trade-off (Stearns 1992). Several studies have clearly demonstrated the negative effects of large family size on child health outcomes (Hagen et al 2006;Lawson and Mace 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has shown that larger sibships lead to dilution of resources directed toward children and grandchildren (Coall et al 2009;Lawson and Mace 2009), reflecting the dynamics of a quality-quantity trade-off (Stearns 1992). Several studies have clearly demonstrated the negative effects of large family size on child health outcomes (Hagen et al 2006;Lawson and Mace 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Cooney & Uhlenberg [86] for example, have reported that number of siblings is negatively related to a range of later investments including the direct receipt of money or gifts, giving advice in difficult decisions and direct assistance with childcare (see also [87]). Keister [88] has also demonstrated that number of siblings has a strong negative influence on the likelihood of receiving a trust fund or an inheritance.…”
Section: Parental Investment and Fertility Declinementioning
confidence: 99%
“…This possible grandparental effect can be expected to vary with the ecological and the socioeconomic circumstances of the family, and also with the sex and the lineage of the grandparents. Based on Hamilton's rule, inclusive fitness can be increased through the individual's own reproduction or by supporting reproduction among genetically closely related kin (Coall et al 2009). …”
Section: Inclusive Fitness and Grandparental Investmentmentioning
confidence: 99%